الصبر في القرآن الكريم وأثره في بناء الشخصية السليمة: دراسة موضوعية مقاصدية - Thabet Ahmad Abu-Alhaj; Sedek Arrifin; Mohammed Abdul Faiz (USIM Press, 2024)
Vol. 17 No. 1 (2021): Journal of Maʿālim al-Qurʾān wa al-Sunnah